TINGKAT PEMAHAMAN GURU TAMAN KANAK-KANAK (TK) TENTANG KEMAMPUAN BERBAHASA ANAK USIA 4-6 TAHUN - Nurbiana Dhieni, Azizah Muis (JIV-Jurnal Ilmiah Visi, 2012)
The research aims at describing the insight level of the Kindergarten Teachers in Jakarta on the language competence of the 4-6 years aged children. Employing survey method, the research selected 100 teachers undertaking PLPG as samples. The research was conducted as from May to July 2012. Having analyzed the data, the research found the highest score is 71 and the lowest is 38. It concludes the insight of Kindergarten teachers on the language competence of 4-6 years aged children in Jakarta still low.